2015
DOI: 10.1016/j.ygyno.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality among women with epithelial ovarian cancer

Abstract: Objectives Patients with solid tumors are at greatest risk for dying from their cancers in the five years following diagnosis. For most malignancies, deaths from other chronic diseases begin to exceed those from cancer at some point. As little is known about the causes of death among long-term survivors of ovarian cancer, we examined causes of death by years from diagnosis. Methods The Surveillance, Epidemiology, and End Results (SEER) database was used to identify women diagnosed with ovarian cancer between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…Our results are consistent with those previously reported using Surveillance Epidemiology and End Results (SEER) data 3. We observed that the proportion of deaths from ovarian cancer decreased dramatically with increasing years since diagnosis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with those previously reported using Surveillance Epidemiology and End Results (SEER) data 3. We observed that the proportion of deaths from ovarian cancer decreased dramatically with increasing years since diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…There may also be misclassification if the physician signing the cause of death is not aware of ovarian cancer, and thus assigns a secondary cause (eg, bowel obstruction) as the primary cause of death despite the fact that the obstruction resulted from the cancer. However, given the consistency in the proportion of women with ovarian cancer as their primary cause of death with prior research,3 we expect this misclassification was minimal. Second, while we chose to report major groups of causes of deaths, we ended up with nearly 100 deaths that were from unclassified causes.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…While significant advancements in treatment therapies and success rates have been observed in some cancers, there has been no significant progress in ovarian cancer treatment over the past 50 years. 3,4 Much of this failure arises from the lack of early detection capabilities, with 60%-70% of all patients diagnosed at advanced stages (III or IV), 1,[5][6][7][8] and an 85% recurrence rate. 9 Ovarian cancer is categorized by the cell of origin, with approximately 90% originating from epithelial cells.…”
Section: Introductionmentioning
confidence: 99%